Canine Gestational Diabetes: A Comprehensive Systematic Review of Pathophysiology, Diagnostics, Treatment, and Prognosis - Adil, Aftab; Prasad, Anupa; Dash, Subrat Kumar; Tigga, Gloria; Verma, Risikesh Kumar (Journal of Neonatal Surgery, 2025)
Background: Gestational diabetes mellitus (GDM) in dogs is an uncommon yet clinically relevant metabolic disorder, with a reported prevalence of approximately 0.05%–0.1% in pregnant bitches presenting to veterinary practices [1]. The pathogenesis is driven by gestational insulin resistance, largely induced by elevated levels of progesterone and placental growth hormone (GH), both of which function as insulin antagonists [2]. These hormonal changes diminish peripheral glucose uptake, leading to sustained hyperglycemia, particularly in dogs with underlying genetic or metabolic susceptibility [3]. If untreated, GDM can result in significant maternal and fetal complications, including maternal ketoacidosis (30%), macrosomia (20–35%), stillbirth (15–22%), and dystocia (up to 40%) [4,5]. Objective: To systematically review the epidemiology, pathophysiology, diagnostic modalities, treatment protocols, and maternal-fetal outcomes associated with GDM in dogs. Materials and Methods: A comprehensive search was conducted across PubMed, ScienceDirect, and Scopus databases for literature published between January 2000 and April 2024. Search terms used included “canine gestational diabetes,” “pregnancy-induced hyperglycemia,” “insulin resistance in dogs,” and “canine reproductive endocrinology” [6]. Inclusion criteria encompassed original peer-reviewed studies, case series, and clinical trials involving canine GDM, with full-text availability in English. Review articles lacking primary data, in vitro experiments, and studies on non-canine species were excluded. A total of 17 studies involving 85 GDM-affected bitches were included. Data extraction followed PRISMA 2020 standards, focusing on hormonal profiles (progesterone, GH), fasting glucose levels, treatment modalities (insulin type, dosage, duration), and clinical outcomes [7,8]. Results: Findings indicate that GDM in dogs primarily arises during late gestation due to heightened progesterone and placental GH levels, culminating in insulin resistance. Diagnostic hallmarks included fasting blood glucose levels ranging from 180–320 mg/dL and persistent glycosuria. Insulin therapy, most commonly NPH or lente insulin at dosages of 0.25–0.5 IU/kg twice daily, was employed in 95% of cases. Successful glycemic regulation was associated with live birth rates of 80–85%, whereas poor control led to higher incidences of stillbirth (15–22%) and dystocia (40–50%). Postpartum follow-up revealed that hyperglycemia resolved in 92% of cases, underscoring the transient nature of the condition. Conclusion: Although rare, GDM in dogs presents a notable risk to both maternal and fetal health. Early diagnosis and effective insulin therapy significantly enhance reproductive outcomes. Routine screening in high-risk pregnancies is recommended. Further large-scale, prospective studies are necessary to establish canine-specific diagnostic criteria and standardized treatment protocols [13,14].